Plant growth-promoting rhizobacteria enhance active ingredient accumulation in medicinal plants at elevated CO2 and are associated with indigenous microbiome - Ng, Charles Wang Wai; Yan, Wen Hui; Xia, Yi Teng; Tsim, Karl Wah Keung; To, Justin Chun Ting (Frontiers in Microbiology, 2024)
Plant growth-promoting rhizobacteria (PGPR) and elevated CO2 (eCO2) have demonstrated their individual potential to enhance plant yield and quality through close interaction with rhizosphere microorganisms and plant growth. However, the efficacy of PGPR under eCO2 on rhizosphere microbiome and, ultimately, plant yield and active ingredient accumulation are not yet fully understood. This study investigated how the medicinal plant Pseudostellaria heterophylla (P. heterophylla) and its rhizosphere microbes respond to PGPR (Bacillus subtilis and Pseudomonas fluorescens) at eCO2 (1000 ppm). It was found that the yield and active ingredient polysaccharides accumulation in the tuber of P. heterophylla were significantly increased by 38% and 253%, respectively. This promotion has been associated with increased root development and changes in the indigenous microbial community. Metagenomics analysis revealed a significant reduction in pathogenic Fusarium abundance in the rhizosphere. Potential biocontrol bacteria Actinobacteria and Proteobacteria were enriched, especially the genera Bradyrhizobium and Rhodanobacter. The reshaping of the rhizosphere microbiome was accompanied by the upregulation of biological pathways related to metabolite biosynthesis in the rhizosphere. These modifications were related to the promotion of the growth and productivity of P. heterophylla. Our findings highlighted the significant role played by PGPR in medicinal plant yield and active ingredient accumulation when exposed to eCO2.